(untitled) (Journal of Medicine, 2023)
Background: Sepsis is a complex, life-threatening, heterogeneous infectious disease associated with increased rates of morbidity and mortality. Early assessment of the prognosis of sepsis is key to achieving a favorable outcome for the disease. This study aimed to identify the prognostic value of PCT for sepsis patients. Materials and Methods: We conducted a prospective analytical study involving 100 adult patients with sepsis who were admitted to the Medicine dept and intensive care unit from 2019 to 2020. At least one blood test for PCT level was performed for all patients within the first 24 hours of suspecting an infection. Results: Our study found that a maximum number of patients (43.0%) were between 51-60 years age group, mean age of the patient was 49.35 ± 11.7 years. Out of 100 cases, 65% were male and 35% were female. The male and female ratio was 1.85:1. In this study serum, procalcitonin levels 0.5-2.0 ng/were detected in 15.0% of patients with mean±SD 1.3±0.8. Serum procalcitonin levels 2.1-10.0 ng/mL were detected in 29.0% of patients with mean±SD 5.9±2.5 and >10.0 ng/mL was detected in 56 patients. Based on the receiver-operator characteristic (ROC) curves, procalcitonin had the area under curve 0.923, with 89.4% sensitivity and 87.5% specificity. In our study, procalcitonin showed the best predictive value for the short-term outcome of sepsis with a cut-off value of 14.8 ng/mL (AUC 0.923). Study shows that 76.0% of the patients recovered completely, but 24.0% of patients expired during the hospital stay. Conclusion: There was a statistically significant correlation in serum procalcitonin with the outcome of sepsis (p < 0.001). So the effectiveness of serum procalcitonin has proven significant in the prediction of mortality in sepsis patients. J MEDICINE 2023; 24: 18-22